New taxonomic notes on the genus Spilogona Schnabl, 1911 (Diptera: Muscidae) in Arctic Russia, with the description of three new species - Sorokina, Vera S. (Zootaxa, 2025)
Three new Spilogona species are described from Franz Josef Land and Wrangel Island (Spilogona hennigi sp. nov., Spilogona gorodkovi sp. nov., Spilogona latizygoma sp. nov.). Ten new synonymies are proposed: Spilogona contigua Huckett, 1965, syn. nov. of Limnophora (Spilogona) ciliatocosta Schnabl in Becker et al., 1915; Spilogona dorsostriata Huckett, 1965, syn. nov. of Scatocoenosia cordyluraeformis Schnabl in Becker et al., 1915; Spilogona albinepennis Huckett, 1965, syn. nov. of Scatocoenosia cordyluraeformis Schnabl in Becker et al., 1915; Limnophora (Spilogona) reflecta Huckett, 1932, syn. nov. of Aricia depressula Zetterstedt, 1845; Spilogona compacta Huckett, 1965, syn. nov. of Limnophora (Spilogonoides) lapponica Ringdahl, 1932; Spilogona perambulata Huckett, 1965, syn. nov. of Spilogona padlei Huckett, 1965; Limnophora (Spilogona) albisquama Ringdahl, 1932, syn. nov. of Limnophoa (Spilogona) pusilla Huckett, 1932; Spilogona barrowensis Huckett, 1965, syn. nov. of Limnophora (Spilogona) quinquesetosa Schnabl in Becker et al., 1915; Tetramerinx brevicornis Malloch, 1917, syn. nov. of Limnophora (Spilogona) scutulata Schnabl in Schnabl & Dziedzicki, 1911; Spilogona coactilis Huckett, 1965, syn. nov. of Spilogona wrangeli Hennig, 1959. Spilogona churchillensis Huchett, 1965 and Limnophora (Spilogona) subfuscisquama Ringdahl, 1932 are restored from synonymy. An error on the determination label of Spilogona fulvibasis Huckett, 1965 is indicated. The new distribution of Spilogona tendipes (Malloch, 1920) is discussed. The identification couples to some similar species are given. Images of some species and of the male terminalia are given. The cytochrome oxidase I gene sequences (CO1) of Russian specimens of one new species and 35 other species are provided and discussed. Total 71 sequences are provided.